The Effect of Copper (II) Nitrate Addition and Tensile Stress on SCC of C44500 Material Tube - Farhan Adi Farrasandi; Firmansyah Sasmita; Husaini Ardy (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2021)
The heat exchanger is an intermediary for two or more fluids that flow both inside and outside of the heat exchanger to distribute heat. This process was aimed to increase efficiency levels in the process industry. One of the suitable materials for the tube is UNS C44500, also known as admiralty brass consists of 70Cu-30Zn, which has high thermal conductivity and good corrosion resistance. However, admiralty brass was susceptible to stress corrosion cracking (SCC) when faced with nitrate since the tube was also loaded by internal stress. Moreover, SCC was also exacerbated by dezincification. The C-ring test method examined the effect of nitrate compounds and dezincification on SCC in C44500 Tube components. Tensile stresses varied between 15, 45, and 85% of yield strength, which were immersed into nitrate solutions consisting of NaNO3 and Cu(NO3)2. Some specimens were washed using 20% ​​HCl to bring up dezincification. The results obtained that SCC occurred at the highest Cu(NO3)2 concentration, identified by longitudinal crack and passivity breakdown. All of the dezincified specimens were found cracked due to SCC after immersion into 1 M Cu (NO3)2, while un-dezincified were failed when given tensile stress between 45% to 85% of maximum yield strength.